2022
DOI: 10.1186/s12890-022-01891-6
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in elderly people with chronic obstructive pulmonary disease in relation to the use of long-term home oxygen therapy: a qualitative study about feelings attributed to therapy

Abstract: Background Elderly people are more likely to suffer severe chronic obstructive pulmonary disease (COPD) and require long-term home oxygen therapy (LTOT) as part of their treatment. LTOT has advantages such as improvement in symptoms, but there are also disadvantages such as physical barriers, psychosocial barriers and emotional challenges. The aim of this study is to understand the experiences of elderly people with COPD using LTOT with respect to their feelings attributed to therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
0
6
0
4
Order By: Relevance
“… 18 19 Bueno et al found that LTOT in elderly patients is associated with poor self-image and leads to sadness and discouragement. 20 In a similar study, Hill et al showed that anxiety’s prevalence is unrelated to using domiciliary oxygen. Our finding contrasts the observations made by Eaton et al, where it was seen that although there is a high prevalence of anxiety and depression in severe COPD, there appears to be a decreasing trend in psychological stress after initiating LTOT.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 18 19 Bueno et al found that LTOT in elderly patients is associated with poor self-image and leads to sadness and discouragement. 20 In a similar study, Hill et al showed that anxiety’s prevalence is unrelated to using domiciliary oxygen. Our finding contrasts the observations made by Eaton et al, where it was seen that although there is a high prevalence of anxiety and depression in severe COPD, there appears to be a decreasing trend in psychological stress after initiating LTOT.…”
Section: Discussionmentioning
confidence: 96%
“…Patients’ worsening anxiety and depression could be related to poor physical health, concerns about imminent death, persistent dyspnoea, severe functional limitation, dependency and burden on family members, and reduced exercise capacity 18 19. Bueno et al found that LTOT in elderly patients is associated with poor self-image and leads to sadness and discouragement 20. In a similar study, Hill et al showed that anxiety’s prevalence is unrelated to using domiciliary oxygen.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de auxiliar na rápida captação de dados, é pouco indicada por, muitas vezes, não apresentar os sujeitos com maior capacidade de fornecimento de dados ricos e substanciais à pesquisa (BLANCO; CASTRO, 2007). Numa investigação científica sobre os sentimentos em idosos com Doença Pulmonar Obstrutiva Crônica (DPOC) em uso de Oxigenoterapia Domiciliar Prolongada (ODP), todos os participantes que atenderam essas características (maiores de 60 anos, com DPOC e uso de ODP), que faziam retorno no Ambulatório de Pneumologia, foram prontamente abordados pelo pesquisador e aceitaram participar da pesquisa, foram incluídos na amostra e entrevistados (BUENO et al, 2022).…”
Section: Conveniênciaunclassified
“…Despite several reports on the efficacy and compliance to LTOT in patients, most studies have focused on physicians’ views of prescription patterns or medical efficacy [ 8 , 9 ]. Only a few studies have considered the patients’ perspectives, usually using text analysis of structured interviews [ 13 , 14 ]. These studies showed that patients use oxygen as a tool for symptom management; however, the improvement in breathlessness by oxygen does not always meet expectations as perceived by patients.…”
Section: Introductionmentioning
confidence: 99%